Development of a demand feeding system for grouper juveniles – (1) Orange-spotted grouper - Mukai, Yukinori; Tan, Nai Han; Liau, Chung Fan (2012)
Demand feeding is a new method by which fish can feed themselves. Fish switch on the feeding device when they require food. This method has several advantages because the fish can eat when they are most motivated to feed. The system can thus minimize feed loss and reduce water pollution. The demand feeding system has been studied for ten years, but so far, there are only a few commercialized feeding devices. Currently, the most urgent issue facing Orange-spotted grouper, Epinephelus coioides, also known as green grouper is an economically important fish species in China and Southeast Asian countries for mariculture.